2003
DOI: 10.1002/syn.10271
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine responsiveness to drugs of abuse: A shell‐core investigation in the nucleus accumbens of the mouse

Abstract: The existence of subterritories within the nucleus accumbens has now been widely supported by histochemical, neurochemical, electrophysiological, as well as morphological and ultrastructural studies and suggest specific afferent and efferent systems involved in different behavioral aspects. Microdialysis studies in the rat have consistently shown that most drugs of abuse increase extracellular dopamine levels preferentially in the shell subregion of the nucleus accumbens. The study of the relative roles of NAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 54 publications
3
36
4
Order By: Relevance
“…Two previous microdialysis studies have evaluated the effects of nicotine on mesolimbic dopaminergic activity in mice. A high dose of nicotine (0.8 mg/ kg) produced a slight increase in DA levels but only when the probe was located in the shell region of the nucleus accumbens (Zocchi et al, 2003). In the second study, nicotine at the dose of 1 mg/kg increased DA levels in an area shown as the ventral pallidum (Marubio et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Two previous microdialysis studies have evaluated the effects of nicotine on mesolimbic dopaminergic activity in mice. A high dose of nicotine (0.8 mg/ kg) produced a slight increase in DA levels but only when the probe was located in the shell region of the nucleus accumbens (Zocchi et al, 2003). In the second study, nicotine at the dose of 1 mg/kg increased DA levels in an area shown as the ventral pallidum (Marubio et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, these results clearly reveal that opioid peptides derived from preproenkephalin are involved in the modulation of nicotinerewarding properties. Nicotine, like most drugs of abuse, activates the mesocorticolimbic dopaminergic system and increases extracellular DA levels in the NAc (Di Chiara and Imperato, 1988;Pontieri et al, 1996;Zocchi et al, 2003), a feature that has been related to its rewarding properties. Accordingly with our behavioral approach, in vivo microdialysis experiments showed that the enhancement in DA efflux in the NAc induced by nicotine (0.5 mg/kg) in wild-type mice was significantly attenuated in preproenkephalin knock-out animals.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological, pharmacological, and genetic experiments have established a clear role for DA in voluntary ethanol consumption (eg, Koob et al, 1994;El-Ghundi et al, 1998;Phillips et al, 1998). For example, SA of ethanol increases nucleus accumbens (Nac) DA release in rodents (Weiss et al, 1993(Weiss et al, , 1996Gonzales and Weiss, 1998;Nurmi et al, 1998;Olive et al, 2000;Melendez et al, 2002;Hungund et al, 2003), and DA D1 and D2 receptor agonists and antagonists modulate ethanol SA in some circumstances (Weiss et al, 1990;Hubbell et al, 1991;Dyr et al, 1993;Rassnick et al, 1993a;Ng and George, 1994;Silvestre et al, 1996;Cohen et al, 1998Cohen et al, , 1999Boyce and Risinger, 2002;D'Souza et al, 2003;Zocchi et al, 2003). In addition, genetic deletion of D1 or D2 DA receptors decreases ethanol SA (El-Ghundi et al, 1998;Phillips et al, 1998;Risinger et al, 2000).…”
Section: Ne and Ethanol Samentioning
confidence: 99%
“…For example, chemical lesions of the NE system, blocking NE synthesis via DBH inhibitors, or genetic deletion of DBH will reduce voluntary ethanol intake, whereas DA lesions do not Kiianmaa et al, 1979;Rassnick et al, 1993b;Weinshenker et al, 2000). Again, evidence does suggest that pharmacologic or genetic manipulation of D1 and D2 receptors can modulate ethanol SA in some circumstances (Weiss et al, 1990;Hubbell et al, 1991;Dyr et al, 1993;Rassnick et al, 1993a;Ng and George, 1994;Silvestre et al, 1996;Cohen et al, 1998Cohen et al, , 1999El-Ghundi et al, 1998;Phillips et al, 1998;Risinger et al, 2000;Boyce and Risinger, 2002;D'Souza et al, 2003;Zocchi et al, 2003). Further research teasing out the specific mechanisms of noradrenergic modulation of opioid and ethanol reward will be required to distinguish between DA-dependent and DA-independent pathways.…”
Section: Some Effects Of Ne On Drug Responses May Be Independent Of Damentioning
confidence: 99%
“…The NAc shell receives dopaminergic efferents of the ventral tegmental area (VTA). This pathway is often referred to as the mesolimbic dopaminergic system and has been implicated in alcohol and drug addiction (Robbins and Everitt, 1996;Wise, 1996;Weiss et al, 1993;Nestler, 2001;Hodge et al, 1997;Zocchi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%